Study The Effects of Circadian Rhythms on Some Liver Function Parameters in Local Iraqi Sheep - Mohammed Asker (Basrah Journal of Veterinary Research)
Objective, The purpose of this experiment is to study the circadian rhythm of common liver function tests. Materials and Methods, Ten adult sheep (male and female) were divided into two groups, T1 (male) and T2 (fe-male), and placed in two separate rooms. Serum was isolated from T1 and T2 blood samples taken at 7, 12 A.M. and 12 P.M hours, respectively.Results, Serum alanine aminotransferase (ALT) and creatinine levels in both groups increased significantly during daylight hours (12:00). The aspartate aminotransferase (AST) showed a different value in a male that increased significantly at 12 A.M. but in a fe-male that was elevated at 7 A.M. as compared with other times. Serum urea concentra-tion during the night hours was expressed at a high level in both males and females as compared to the concentration during the day hours. In addition, the results show differences in variation between males and females. There is a significant increase in ALT, urea and creatinine in females (T2) as compared with males (T1) during the day and night hours. Furthermore, at 12 A.M. and 12 P.M., males had significantly higher AST levels than females Conclusion, liver functions cause variations between day and night hours as well as between males and females because of metabolism and activities. Comprehensive study is required to reduce and overlap this stress.